A Context-Responsiveness Framework for the Relationship Between Government and Social Entrepreneurship: Exploring the Cases of United States, Switzerland, and Lithuania. Issue 5 (3rd September 2019) - Erpf, Philipp; Bryer, Thomas Andrew; Butkevičienė, Eglė
Abstract: In this article, we consider the status of social entrepreneurship and social enterprise in relation to government and public administration practice. For this purpose, we present and discuss a framework composed of three alignments. In the first alignment, social entrepreneurial practices and supportive policies, to the extent they exist, are fully bracketed within sociohistorical traditions of the place and cultural traditions of the people and groups in society. In the second alignment, governments have established or are in the process of establishing systems reforms to promote social entrepreneurial behavior that link specific policy interventions, or sociocultural interventions, with a normatively desired environment. This includes making system reforms that strive to break away from the historical and cultural biases that may have restrained social enterprises and in which legal, social, political, and economic interventions are fully aligned with one another. In the third alignment, the reforms designed and implemented are focused on the specific objectives that can enable and facilitate social entrepreneurial behavior like access to human and financial capital, access to markets for products and/or services developed, access to government decision makers who are responsible for establishing environments, and/or policies conducive to social entrepreneurial behavior and ventures. We selected three countries, United States, Switzerland, and Lithuania, as illustrations for our framework, given their highly divergent sociohistorical contexts, current governance structures, and comfort with various ideals and excesses of capitalist and social-democratic systems. This exploration gives the reader a foundational understanding of the concept and divergent approaches to implementation of a social-entrepreneurial cultural and policy framework.